PARTISIPASI PEREMPUAN PADA LEMBAGA LEGISLATIF TAHUN 2014-2019 DI PROVINSI JAWA TIMUR - Ani Purwanti (Masalah-Masalah Hukum, 2015)
Temporary special measures or positive discrimination on woman participation in legislatives, or known as affirmative action has been established since 2004 by Political Party and Legislative Acts packages. This research is using qualitative methods with socio-legal approach, which is combining the two aspects: regulation aspect and non-regulation aspect. It is necessary to combine those two aspect to put the text on the context; relation between law and its underpinned implementation on society. The result from this research show that on 2004, the number of East Java Province Legislative’s members were 100, consists of 85 person male and 15 person female. On the district level, Surabaya is the highest number of woman representation by 34% (17 from 50), Madiun 33,3% (10 from 30), Kediri 33,3% (10 from 30, and Probolinggo 33,3% (10 from 30). The lowest precentage were Bangkalan, Sampang, and Pasuruan whose woman’s precentation were below 3%. The main factor of the low women legislative’s representation number were the patriarch culture, the image of domestic women instead of their public-political actions effecting both of the women electability, male-dominated political party’s culture and their political participation itselfKebijakan khusus dikenal dengan prinsip “ Affirmative Action “ atau diskriminasi positif  telah diterapkan pada UU Partai Politik dan UU Pemilu Legislatif.  Affirmative Action bersifat sementara, sehingga apabila tujuan dan sasaran untuk mencapai kesetaraan telah tercapai atau kelompok-kelompok yang dilindungi telah terintegrasi, maka kebijakan tersebut tidak lagi diterapkan. Metode yang digunakan adalah dengan pendekatan sosio legal research, Penelitian sosio legal dipilih karena dalam penelitian ini akan dilihat teks dan konsteksnya, juga akan dilihat bagaimana implementasi dan relasi antara UU dengan masyarakat sekitar. Hasil penelitian menunjukkan di DPRD di Provinsi Jawa Timur terdapat 15 perempuan dari 100 anggota, laki laki 85, sehingga representasi perempuan sebesar 15%.  Kota Surabaya mempunyai representasi 34% (17 dari 50), Madiun 33,3%, Kediri 33,3%, Probolinggo 33,3%, Sampang 2,2%, Pasuruan  3,3% ( 1 dari 30) serta  Bangkalan 0%. Faktor utama rendahnya representasi adalah budaya patriarkhi yang berkelindan diantara stakeholder, yaitu Partai Politik, perempuan dan masyarakat pemilih